1996
DOI: 10.1017/s0043174500093838
|View full text |Cite
|
Sign up to set email alerts
|

Smallseed Dodder (Cuscuta planiflora) Phototropism toward Far-red When in White Light

Abstract: White light-grown seedlings of smallseed dodder were (a) provided with unilateral far-red (700 to 800 nm) at photon irradiances ranging from 20 to 110 μmol m−2 s−1 against a background of cool white light (400 to 700 nm) from above at 77 μmol m−2 s−1, or (b) transferred to darkness and provided with unilateral white light at 20 μmol m−2 s−1, unilateral blue light (400 to 500 nm) at 10 μmol m−2 s−1, unilateral red light (600 to 700 nm) at 10 μmol m−2 s−1, unilateral far-red at 50 μmol m−2 s−1, or (c) in experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
(16 reference statements)
1
40
0
Order By: Relevance
“…In addition, blue light photoreceptors that can perceive blue light gradients in the canopy are also involved in the shade-avoidance response (Ballaré 1999). However, dodders show a positive phototropism to lateral light signals with a lower R/FR ratio to find parasitic hosts, and blue or far red light can induce dodders to entwine their hosts and develop haustoria (Orr et al 1996;Tada et al 1996). Previous studies suggest that both phytochromes and crytochromes may be involved in the twining response of dodder (Lane and Kasperbauer 1965;Tada et al 1996;Haidar 2003).…”
Section: Proteins Related To Light Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, blue light photoreceptors that can perceive blue light gradients in the canopy are also involved in the shade-avoidance response (Ballaré 1999). However, dodders show a positive phototropism to lateral light signals with a lower R/FR ratio to find parasitic hosts, and blue or far red light can induce dodders to entwine their hosts and develop haustoria (Orr et al 1996;Tada et al 1996). Previous studies suggest that both phytochromes and crytochromes may be involved in the twining response of dodder (Lane and Kasperbauer 1965;Tada et al 1996;Haidar 2003).…”
Section: Proteins Related To Light Signal Transductionmentioning
confidence: 99%
“…However, these chemical signals may be used only by certain species of root parasites, and it is still unknown whether stem parasites such as dodders require such chemical signals for parasitism. Many other studies suggest that light qualities and duration are the major signals for inducing the twining response and haustoria formation in dodders (Lane and Kasperbauer 1965;Furuhashi et al 1995;Tada et al 1996;Orr et al 1996;Haidar 2003). It has been shown that dodder seedlings tend to grow toward light sources with low red/far red (R/FR) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Being an obligate stem parasite, young Cuscuta spp. seedlings must be able to detect, evaluate and respond to the quality, quantity and direction of light in order to survive (Orr et al. , 1996; Haidar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Young dodder seedlings, prior to host attachment, are influenced by light: seedling de-etiolation (Haidar et al, 1997), circumnutation (Dawson et al, 1994), host detection (Orr et al, 1996a), gravitropism (Orr et al, 1996b), and induction of coiling and prehaustoria development (Haidar et al, 1997;Lane & Kasperbauer, 1965;Zimmerman, 1962). seedlings is determined by competence in detecting, evaluating, and responding to light quality, quantity and direction.…”
Section: Introductionmentioning
confidence: 99%